DOCHODZENIE ZAWARCIA UMOWY PRZYRZECZONEJ W OBROCIE NIERUCHOMOŚCIAMI. ZABEZPIECZENIE I PRZEDAWNIENIE ROSZCZEŃ - Mróz, Arkadiusz (Zeszyty Prawnicze, 2016)
Assertion of the Conclusion of a Promised Contract in Property Trading. Securing and Limitation of Claims Summary This is the last of three articles presenting a detailed discussion of the legal construction of the preliminary agreement, as well as its significance and potential application in property trading. It presents the contracting party’s possibility of making a claim concerning the conclusion of a promised contract; and the securing of claims by the obliged party’s grant of a power of attorney for the conclusion of the promised contract on his behalf and in his favour, and by the entry of the claim in the land and mortgage register. The article also discusses the limitation of claims on a preliminary agreement. The article ends with a summary of the conclusions drawn from all three articles.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />